Hsp78 (78 kDa Heat Shock Protein), a Representative AAA Family Member Found in the Mitochondrial Matrix of Saccharomyces cerevisiae - Abrahão, Josielle; Mokry, David Z.; Ramos, Carlos H. I. (Frontiers in Molecular Biosciences, 2017)
ATPases associated with diverse cellular activities (AAA+) form a superfamily of proteins involved in a variety of functions and are characterized by the presence of an ATPase module containing two conserved motifs known as Walker A and Walker B. ClpB and Hsp104, chaperones that have disaggregase activities, are members of a subset of this superfamily, known as the AAA family, and are characterized by the presence of a second highly conserved motif, known as the second region of homology (SRH). Hsp104 and its homolog Hsp78 (78 kDa heat shock protein) are representatives of the Clp family in yeast. The structure and function of Hsp78 is reviewed and the possible existence of other homologs in metazoans is discussed.